Demographics and the Politics of Capital Taxation in a Life-Cycle Economy - Mateos-Planas, Xavier (American Economic Review, 2010)
This article studies the effects of demographics on the mix of tax rates on labor and capital. It uses a quantitative general-equilibrium, overlapping-generations model where tax rates are voted without past commitments in every period and characterized as a Markov equilibrium. In the United States, the younger voting-age population in 1990 compared to 1965 accounts for the observed decline in the relative capital tax rate between those two years. A younger population raises the net return to capital, leads voters to increase their savings, and results in a preference for lower taxes on capital. Conversely, aging might increase capital taxation. (JEL E13, H24, H25, J11)